RAFT alcoholic dispersion polymerization with polymerization-induced self-assembly - Lowe, Andrew (Elsevier Ltd, 2016)
© 2016 Elsevier Ltd. This article reviews the current state of the art with respect to RAFT alcoholic dispersion polymerization processes that proceed with polymerization-induced self-assembly (PISA) and covers the bulk of the literature up to mid-2016. The article is arranged according to suitable comonomers that may employed in such copolymerizations. Where appropriate we have highlighted unusual nanoparticle morphologies that are accessible, and formulation specific, as well as interesting properties associated with certain final nano-objects.